The influence of microtexture on the formation mechanism of nodules in Zircaloy-4 alloy tube. (15th June 2020) - Zhang, Yingdong; Yuan, Fusen; Han, Fuzhou; Ali, Muhammad; Guo, Wenbin; Li, Geping; Liu, Chengze; Gu, Hengfei
Abstract: Corrosion resistance of Zircaloy-4 alloy tube in superheated steam at 673 K/10.3 MPa is anisotropic. A part of the surface undergoes uniform corrosion while the other suffers nodular corrosion. Narrow and wide nodules are observed after an exposure period of 3 and 30 days, respectively. A new matrix transformation method is established in order to study the formation mechanism of nodules in the cross-section (CS) of Zircaloy-4 alloy tube using the EBSD technique, while the CS perpendicular to axial direction (AD). The results reveal that the microtexture is a key factor behind the two types of corrosion. Furthermore, the oxide layers grow anisotropically over the corroded surface. A thick oxide layer forms over the nodular corrosion region on the grains with c-axis oriented in the range of 40° around tangential direction (TD), whereas a thin oxide layer over the uniform corrosion region is detected on the grains with c-axis oriented in the range of 68° around TD. In short, the anisotropic growth of oxide layer was caused by the change of microtexture of the Zr-4 alloy tube, and this anisotropic growth of oxide layer contributed to the nodules formation.